[Indirect Taxes and Relative Prices]: Reply - Friedlaender, Ann F. (Quarterly Journal of Economics, 1968)
Journal Article Indirect Taxes and Relative Prices: Reply Get access Ann F. Friedlaender Ann F. Friedlaender Boston College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 82, Issue 2, May 1968, Pages 344–345, https://doi.org/10.2307/1885903 Published: 01 May 1968